Enhanced Open‐Circuit Voltage in Colloidal Quantum Dot Photovoltaics via Reactivity‐Controlled Solution‐Phase Ligand Exchange. Issue 43 (9th October 2017) - Jo, Jea Woong; Kim, Younghoon; Choi, Jongmin; de Arquer, F. Pelayo García; Walters, Grant; Sun, Bin; Ouellette, Olivier; Kim, Junghwan; Proppe, Andrew H.; Quintero‐Bermudez, Rafael; Fan, James; Xu, Jixian; et al.
Abstract: The energy disorder that arises from colloidal quantum dot (CQD) polydispersity limits the open‐circuit voltage ( V OC ) and efficiency of CQD photovoltaics. This energy broadening is significantly deteriorated today during CQD ligand exchange and film assembly. Here, a new solution‐phase ligand exchange that, via judicious incorporation of reactivity‐engineered additives, provides improved monodispersity in final CQD films is reported. It has been found that increasing the concentration of the less reactive species prevents CQD fusion and etching. As a result, CQD solar cells with a V OC of 0.7 V (vs 0.61 V for the control) for CQD films with exciton peak at 1.28 eV and a power conversion efficiency of 10.9% (vs 10.1% for the control) is achieved. Abstract : A new solution‐phase ligand exchange method for preventing colloidal quantum dots fusion and etching is developed via judicious incorporation of reactivity‐engineered additives. This method provides improved monodispersity in final colloidal quantum dot films and thus leads to the significant enhancement of open‐circuit voltages in colloidal quantum dot solar cells.